Analisis Implementasi Program Rumah Desa Sehat Dalam Penurunan Angka Stunting: Studi Kasus Di Desa Margomulyo Kabupaten Kendal - Agus Bahrudin; Mayang Rahmanda (Universitas 17 Agustus 1945, 2024)
The implementation of the Healthy Village Home program in Margomulyo Village shows strong integration of the four main factors of policy implementation, namely communication, resources, disposition and organizational structure. This program succeeded in building effective communication by involving the community through the Healthy Village Home as a Community Learning Center. The commitment of the village government and assistance from Baznas provides significant financial resources, with organized allocation of funds through the Village Revenue and Expenditure Budget and additional support from Baznas. The disposition is seen in active community participation and close collaboration between stakeholders, especially in regular meetings and joint decision making. The organizational structure that was formed with clear legality and defined roles both at the village head level and participation from various elements of society, shows success in building a strong foundation for the program to reduce the stunting rate from 7% to 2% in 2023. Even though this program is faced with obstacles such as low parental awareness and budget limitations, with good commitment and coordination, it is hoped that this program can be effective in reducing the stunting rate in the village. Supporting factors for the program are the commitment of the village government and assistance from Baznas, especially for the Supplementary Food Program .Concrete steps involving the delivery of Supplementary Food Program directly to parents' homes provide personalized support that can increase the sustainability and effectiveness of the program. Inhibiting factors include low parental awareness and limited Village APB budget in the healthy village house program in reducing stunting rates